ANALISIS PEMBELIAN IMPULSIF PRODUK DITINJAU DARI PERSPEKTIF BELANJA HEDONIS, LIVE SHOPPING E-COMMERCE, FASILITAS PAY LATER, DAN LITERASI FINANSIAL (STUDI KASUS GENERASI Z PADA PELAJAR SMK PGRI 1 KUDUS) - Risda Kumala Sari; Supriyono; Ag. Sunarno H (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to analyze the causes and effects of impulsive product purchases from the perspective of hedonic shopping, live shopping e-commerce, pay later facilities, and financial literacy (case study of generation Z students at SMK PGRI 1 Kudus), which then examines what become a supporting and inhibiting factor so that impulse purchases of products made by students of SMK PGRI 1 Kudus decrease. The method used is qualitative using fishbone diagram analysis. Financial health from an early age can determine a person's financial well-being in the future. Normalizing impulsive behavior that is not immediately rehabilitated will become a habit that has a negative impact. SMK PGRI 1 Kudus, as a Vocational High School that promotes personal grooming, makes its students really pay attention to their appearance, so that impulse purchases sometimes occur in the category of appearance supporting products. SMK PGRI 1 Kudus has made efforts to control purchases made by its students in order to reduce impulse purchases of products by continuing to apply personal grooming in its students' daily lives.